BI as a Solution To Boost Higher Education Performance La BI Comme Solution Pour Améliorer la Performance De L'enseignement Supérieur - Belhadj, Meriem (Finance and Business Economies Review, 2019)
From a wide literature review, the reader can conclude that BI can be considered as the best mean to create knowledge in order to develop the insights and understanding needed to make informed decisions. When we talk about the higher education sector, the issue is not different where its purpose is to equip students for success. While HEIs facing increasing pressures from social and economic change, academic quality and performance become more critical than ever. Higher education is under pressure to meet greater expectations, whether for student numbers, educational preparation, and workforce needs, or economic development. Thus, institutions seeking through educational intelligence to gain a competitive advantage that is related to performance indicators and quality indexes. This research in its objectives attempts to impose the idea of how BI concepts can be implemented in the higher education sector as a response to enhance quality and performance levels.